The Effect of Changing the Jurisprudential Characterization of the Policyholders Relationship with the Insurance Account on the Takaful Insurance Contract - Al-Azemi, Mohammad Abdulhdi Marzoq; AL-Khalaf, Mohammad Omar (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aimed to investigate the jurisprudential characterizations of policyholders’ relation with the insurance account. The collaborative Takaful Insurance Contract has been characterized differently; some viewed it based on the recompense between the installment and compensation; others considered it as conditional gift, the vast majority of contemporary scholars characterized it as being a commitment to donation which was supported by the sharia criteria. The Consortium of Islamic Fiqh characterized Takaful Insurance as being a form of collaboration; others conceptualized it based on the wakf or the collaborative recompense. Methods: The research adopted the inductive and the descriptive analytical approaches by screening the various jurisprudential characterizations suggested by the contemporary scholars on the collaborative Takaful Insurance and then described, analyzed and demonstrated the impact on the contract. Results: The jurisprudential characterization adopted by this study is to characterize the Takaful Insurance based on commitment with donation. The study concluded that investment of the insurance surplus doesn’t vary by the jurisprudential characterization. The party that exercises the investment varies by who eventually owns the insurance surplus. The relationship between the subscribers under the collaborative Takaful contract varies by the jurisprudential characterization. As for the sharia governance, the existence of Sharia Control Body is imperative and doesn’t vary by the jurisprudential characterization. Ultimately, the imposition of the Zakat varies by the jurisprudential characterization of the Takaful insurance. Conclusions: There are many jurisprudential characterizations of Takaful Insurance. The variability of such characterizations impacts the collaborative Takaful Insurance in some inherent points.